The role of lateral external fixation in paediatric humeral supracondylar fracture - Ren, Yi Kow; Low, L. C.; Mor Japar Khan, Ed Simor Khan (Crimson Publishers, 2018)
Humeral supracondylar fracture is the most common elbow injury in children. Displaced fractures are often fixed with pinning method after a closed or an open reduction. Recently, lateral external fixation is becoming more popular in the treatment of humeral supracondylar fractures with reported good outcomes. The pros and cons of this new technique are being discussed in this review.